2017
DOI: 10.1021/acs.jpcc.6b11938
|View full text |Cite
|
Sign up to set email alerts
|

Modification of BiOI Microplates with CdS QDs for Enhancing Stability, Optical Property, Electronic Behavior toward Rhodamine B Decolorization, and Photocatalytic Hydrogen Evolution

Abstract: Fast recombination of photoinduced charge carriers is a major problem in the case of semiconductor based photocatalysts, which must be solved for their potential application in photocatalysis. In this work, photostable CdS QDs/BiOI composites have been successfully fabricated by a two-step precipitation–deposition method. The prepared samples were characterized by X-ray diffraction (XRD), UV–vis diffuse reflection spectroscopy (UV–vis DRS), photoluminescence (PL) spectroscopy, transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(111 citation statements)
references
References 58 publications
8
103
0
Order By: Relevance
“…Moreover, the distances of ≈0.200 and ≈0.243 nm correspond to the (400) and (311) planes in the spinel Co 3 O 4 lattice, respectively (Figure H) . Obviously, high crystallinity and ultrasmall particle size will accelerate photogenerated carrier to diffuse toward the surface, thus enhances its photocatalytic activity . Furthermore, both Co 3 O 4 QDs and CNNS are in tight contact with each other to form heterojunction in the interfacial area, which can efficiently retard the photogenerated electron/hole recombination and enhance the possibility of photogenerated charge participating in AOPs.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, the distances of ≈0.200 and ≈0.243 nm correspond to the (400) and (311) planes in the spinel Co 3 O 4 lattice, respectively (Figure H) . Obviously, high crystallinity and ultrasmall particle size will accelerate photogenerated carrier to diffuse toward the surface, thus enhances its photocatalytic activity . Furthermore, both Co 3 O 4 QDs and CNNS are in tight contact with each other to form heterojunction in the interfacial area, which can efficiently retard the photogenerated electron/hole recombination and enhance the possibility of photogenerated charge participating in AOPs.…”
Section: Resultsmentioning
confidence: 57%
“…With the increment of CNNS amount in the Co 3 O 4 /CNNS composites, the peak intensities of the CNNS increase with decreasing Co 3 O 4 intensities. Moreover, the crystallite size of Co 3 O 4 QDs is calculated to be 2.6 nm, according to the Scherrer equation and the prominent (311) diffraction peak, which is smaller than its excitonic Bohr radius (≈5–6 nm) …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The positive slope was observed in the Schottky plots of all the products shown in Additional file 1: Figure S7 which demonstrated that the photocatalysts were assigned to n-type semiconductors [77, 78]. The flat band potentials ( E fb ) of the samples can be estimated using the extrapolation of the Mott-Schottky plot at the frequency of 1000 Hz and found to be − 0.685 eV for the SnNb 2 O 6 , − 0.67 eV for the mixed phases of SnNb 2 O 6 and Sn 2 Nb 2 O 7 , and − 0.626 eV for the Sn 2 Nb 2 O 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Among them, bismuth oxyiodide (BiOI), as a p ‐type semiconductor with narrow band gap energy ( ca . 1.8 eV), has rapidly sparked numerous interest as a protuberant and efficient visible‐light‐driven photocatalyst for solar energy conversion and environmental management owing to its excellent merits of supreme optical and electrical properties, unique layered structure, high dipole moment, high chemical stability, nontoxicity and low cost . More importantly, BiOI has highly anisotropic layered tetragonal matlockite structure with [Bi 2 O 2 ] 2+ slabs interleaved by double slabs of iodine atoms, which are beneficial to impart an internal static electric field between the [Bi 2 O 2 ] 2+ and I ‐ slab along the [001] direction, which is advantageous to the separation of photo‐induced electron hole pairs .…”
Section: Introductionmentioning
confidence: 99%